2008
DOI: 10.4028/www.scientific.net/amr.55-57.429
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Manufacturing Technology and Characterization of Composite Fabric for Stab Resistant Materials

Abstract: d more to their own safety, lead all kinds of personal protection apparatus to rapidly develop. This study designed and manufactured the stabbing resistant fabrics to prevent the pricking damage of human body. In this study, woven Kevlar fabric is laid between two layers of polyamide 6 fibrous webs that contain low-melt polyester fibers. The fibrous webs and woven fabric are bonded via needle punching and thermal bonding to generate a nonwoven/woven composite fabric that can be used as a substrate for artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…All the stabbing weapons listed above can be classified as either edged or pointed. 24,62 Hence, the act of stabbing can be described in terms of cutting or puncturing of materials. Weapons such as knives, tools, swords, and other implements designed to perforate or cut materials have a long continuous cutting edge and are classified as ‘edged’ weapons.…”
Section: Description Of Stab and Spike Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the stabbing weapons listed above can be classified as either edged or pointed. 24,62 Hence, the act of stabbing can be described in terms of cutting or puncturing of materials. Weapons such as knives, tools, swords, and other implements designed to perforate or cut materials have a long continuous cutting edge and are classified as ‘edged’ weapons.…”
Section: Description Of Stab and Spike Threatsmentioning
confidence: 99%
“…They can be used to prepare composite material for stab resistance purposes. 62,106 Unidirectional (UD) fabric is a type of nonwoven fabric prepared with yarns arranged in parallel at 0 /90 angles, together with a flexible resin as the binder, 107,108 whereas in woven fabrics two sets of yarns (warp and weft) are interlaced (Figure 4). UD fabrics can also be prepared by placing yarns at angles different from 0 /90 .…”
Section: Textile Solutionsmentioning
confidence: 99%
“…For Kevlar products, many studies recently focus on improving their puncture resistance and lowering their cost by needle-punching with nonwovens and core-spinning with cotton or coating with inorganic particles etc. [3][4][5]. In this paper, recycled Kevlar fibers are used for the purpose of cost reduction, environmental benefits, and mechanical property reinforcement as well as puncture resistance improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing parameters in nonwoven process have influence on mechanical properties and puncture resistance of nonwoven products. Needle-punching density, hot-pressing temperature, and hot-pressing duration have impact on mechanical and puncture resistance properties of composite nonwovens [3,[5][6][7]. Besides, it is also found that biocomponent low-T m /high-T m polyester fibers content is related to mechanical properties of nonwovens [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Both the projectile and the armor undergo deformation and friction. The projectile's geometry and velocity determine the deformation of the armor's layers (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%